1DTempPro V2: New Features for Inferring Groundwater/Surface‐Water Exchange. Issue 3 (15th September 2015) - Koch, Franklin W.; Voytek, Emily B.; Day‐Lewis, Frederick D.; Healy, Richard; Briggs, Martin A.; Lane, John W.; Werkema, Dale
Abstract: A new version of the computer program 1DTempPro extends the original code to include new capabilities for (1) automated parameter estimation, (2) layer heterogeneity, and (3) time‐varying specific discharge. The code serves as an interface to the U.S. Geological Survey model VS2DH and supports analysis of vertical one‐dimensional temperature profiles under saturated flow conditions to assess groundwater/surface‐water exchange and estimate hydraulic conductivity for cases where hydraulic head is known.